Masquelet technique in military practice: specificities and future directions for combat-related bone defect reconstruction - Mathieu, Laurent; Mourtialon, Romain; Durand, Marjorie; de Rousiers, Arnaud; de l’Escalopier, Nicolas; Collombet, Jean-Marc (Military medical research, 2022)
Because of its simplicity, reliability, and replicability, the Masquelet induced membrane technique (IMT) has become one of the preferred methods for critical bone defect reconstruction in extremities. Although it is now used worldwide, few studies have been published about IMT in military practice. Bone reconstruction is particularly challenging in this context of care due to extensive soft-tissue injury, early wound infection, and even delayed management in austere conditions. Based on our clinical expertise, recent research, and a literature analysis, this narrative review provides an overview of the IMT application to combat-related bone defects. It presents technical specificities and future developments aiming to optimize IMT outcomes, including for the management of massive multi-tissue defects or bone reconstruction performed in the field with limited resources.